2019
DOI: 10.3390/su12010117
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Residential Trees and Awareness of Tree Services and Disservices in a Tropical City

Abstract: Attitudes toward urban residential trees and awareness of their ecosystem services and disservices may play an important role in management decisions of private residential green spaces with important consequences to urban sustainability. In 2011, 397 household surveys were conducted in six locations of the Río Piedras Watershed (San Juan, Puerto Rico) to evaluate residents' attitudes toward residential and neighborhood trees and their association with household socio-demographic factors, how awareness of serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 100 publications
0
14
1
2
Order By: Relevance
“…Ecosystem disservices are poorly studied compared to services [ 71 ] and rarely considered simultaneously with benefits [ 72 , 73 ]. We know of no other research relating core values and environmental attitudes to the perception of disservices, although a few studies have shown that these perceptions may differ cross-culturally [ 74 ], between rural and urban dwellers [ 75 ], across income and ethnic groups [ 76 ], with proximity to the disservice [ 77 ], and among people with different pro-environmental behaviors [ 78 ]. Given the dearth of work on this topic, we are unable to contextualize our finding that disservices were more concerning to people with Egoistic values and Utilizationist attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem disservices are poorly studied compared to services [ 71 ] and rarely considered simultaneously with benefits [ 72 , 73 ]. We know of no other research relating core values and environmental attitudes to the perception of disservices, although a few studies have shown that these perceptions may differ cross-culturally [ 74 ], between rural and urban dwellers [ 75 ], across income and ethnic groups [ 76 ], with proximity to the disservice [ 77 ], and among people with different pro-environmental behaviors [ 78 ]. Given the dearth of work on this topic, we are unable to contextualize our finding that disservices were more concerning to people with Egoistic values and Utilizationist attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The ES or EDS mentioned as reasons for preference or least preference respectively, were deductively coded by one author based on lists from the literature [29][30][31]. The coding process was in accordance with that outlined in Olivero-Lora et al [32]. The ES were assigned to a group in the CICES classification system [31] and EDS were assigned to one of the five categories of EDS proposed in Vaz et al [30].…”
Section: Questionnairementioning
confidence: 99%
“…This may indicate a recognition that urban trees have a common good and contribute to a better quality of life shared by all the citizens, and so trees better suited for that purpose are preferred. Olivero et al [32] noted differences in the recognition of the ES provided by private trees (provisioning) and public trees (cultural). Or alternatively, it may reflect a general knowledge of the challenges of urban forestry gained from the reporting of storm damage from trees in the local media for example [46].…”
Section: Species Preferencesmentioning
confidence: 99%
“…1). These yards are part of a larger project setup established by the San Juan ULTRA Network across the RPWS Urban Ecosystems (Melendez-Ackerman et al 2014Vila-Ruiz et al 2014;Torres-Camacho et al 2017;Olivero-Lora et al, 2019). The RPWS is characterized by a land cover gradient that ranges from highly urbanized areas near the coast to highly forested areas around the headwater and has a mean annual temperature of 25.7º C and a mean annual precipitation that ranges from 1,509 mm in the coast to 1,755 mm in the upland (Lugo et al 2011).…”
Section: Study Sitementioning
confidence: 99%
“…However, residential yards are privately owned and subject to human selective pressures and management that may hinder the recovery of ecosystem services. A prior study shows that yard owners in San Juan have prioritized food production, air purification, ornamental value, and temperature reduction above other services (Olivero-Lora et al 2019). Therefore, decision makers and managers should use these preferences as a guide to develop management plans for these areas.…”
Section: Hurricane-driven Changes In Ecosystem Servicesmentioning
confidence: 99%